(untitled) (Biological Sciences - PJSIR, 1995)
Alpha-amylase, protease, reducing sugars, non-reducing sugars, protein and total amino acids were studied in seedlings of 4 wheat genotypes, for a period of 96 hrs. after sowing, under stressed and non-stressed conditions. It was observed that u-amylase, protease, reducing and non-reducing sugars and total mino acids increased in all the genotypes subjected to -0.6 MPa water stress. The genotypes Chakwal-86 and DS-4 showed the highest a-amylase activity, sugars and total amino acids. On the other hand DS-17 and Pavon showed higher protease activity than the others. The highest reduction in protein content was recorded in DS-17 andPavon. The significance of these findings is-discussed.